To Investigate the Refractive Index of Blood Plasma Suspended in Various Tonicity Solutions - Sumathi, Jogu; Jaleeli, Zeeshan Ahmed; Jaleeli, Kaleem Ahmed; Ahmad, Adeel (Journal for Research in Applied Sciences and Biotechnology, 2022)
This paper reports the data of the RI of plasma of normal blood, which is measured using Abbes' refractometer. The experimental values are compared to normal blood serum erythrocytes with Blood of Plasma suspended in various tonicity solutions between and 1.336 to 1.343, whereas the normal blood plasma refractive index is 1.351. As a result, the refractive index the worth of erythrocytes washed with different tonicity solutions are slightly lower than those of normal blood. If this optical parameter is standardized, it has the potential to be used as a tool in the medical field.